1999
DOI: 10.1038/sj.gt.3300795
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic DNA-compacting peptides derived from human sequence enhance cationic lipid-mediated gene transfer in vitro and in vivo

Abstract: Cationic lipids can deliver genes efficiently in vitro, but are with classical DNA/lipid lipoplexes, and particularly confer generally inhibited by the presence of serum, and their the capacity to transfect in the presence of serum. This efficiency in vivo is much lower than in vitro. An attractive acquisition of serum resistance is cell type-independent, strategy is to induce strong DNA compaction by its associand observed with all four lipopolyamines tested and polyation with proteins, before addition of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 50 publications
(63 reference statements)
5
48
0
Order By: Relevance
“…It has been proposed that this peptide increases lipid-mediated gene transfection by condensing DNA into a compact structure, which promotes cellular entry and stability of DNA. 34,35 The use of this polycation could also improve the in vivo activity of lipoplexes 36,37 and has the additional advantage of being non-toxic in humans. In this study we examined whether a liver-targeted, stable gene transfer system could be constructed by combining the condensing effect of protamine and the targeting capability of AF.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that this peptide increases lipid-mediated gene transfection by condensing DNA into a compact structure, which promotes cellular entry and stability of DNA. 34,35 The use of this polycation could also improve the in vivo activity of lipoplexes 36,37 and has the additional advantage of being non-toxic in humans. In this study we examined whether a liver-targeted, stable gene transfer system could be constructed by combining the condensing effect of protamine and the targeting capability of AF.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the NLS peptides may constitute a valuable tool to improve the efficiency of transgenesis in several species. Several reports confirm the potential use of nuclear targeting peptides, which are non-covalently bound to vector DNA, to enhance the efficiency of biotechnological non-viral gene transfer applications (Malecki, 1996;Aronsohn and Hughes, 1998;Schwartz et al, 1999;Liang et al, 2000;Chan and Jans, 2001).…”
Section: Non-covalent Association Of Dna With Nls Sequence-bearing Symentioning
confidence: 99%
“…However, the use of whole protein might present both production and immunological limitations. Schwartz et al (1999) have devised a system in which DNA is associated with short peptides derived from human histone and protamine, before the addition of any cationic lipid or polymer. Indeed peptides strongly associated with DNA confer to such peptide-DNAlipid particles an enhanced in vitro transfection efficiency over that observed with classical DNA/lipid lipoplexes.…”
Section: Non-covalent Association Of Dna With Nls Sequence-bearing Symentioning
confidence: 99%
“…A number of ternary systems have been described over the past few years, most importantly the lipid:protamine:DNA (LPD) vector systems reported by Huang and coworkers, and others. [6][7][8][9][10][11][12][13][14][15] Other ternary systems involving alternatives to protamine have also been described in the past few years including systems based around poly-L-lysine, 16,17 spermidine, 18 lipopolylysine, 19 histone proteins, 20,21 chromatin proteins, 22 human histone derived peptides, 23 oligo-L-lysine, [24][25][26] L-lysine containing synthetic peptides, 27 and a histidine/lysine (H-K) copolymer. 28 In our case, we chose to use the adenoviral core complex peptide (mu).…”
Section: Introductionmentioning
confidence: 99%